Literasi Digital Islami sebagai Upaya Pencegahan Penyebaran Hoaks Keagamaan di Kalangan Mahasiswa - Mulia Hasnah; Risma Handayani (Jurnal PGSD Universitas Lamappapoleonro, 2026)
Advances in digital technology have made it easier for the public to access and disseminate information, including religious information. However, this ease of access has also been accompanied by an increase in the spread of religious misinformation, which has the potential to cause misunderstandings, social conflict, and distortions in religious understanding. As a group that actively uses digital media, students face a relatively high risk of being exposed to unverified information. Therefore, Islamic digital literacy is a crucial effort in preventing the spread of religious hoaxes among students. This study aims to analyze students’ level of understanding of Islamic digital literacy, identify common forms of religious hoaxes, examine the role of Islamic digital literacy in preventing the spread of religious hoaxes, and identify factors that support and hinder its implementation. This study employs a descriptive qualitative approach using data collection techniques such as in-depth interviews, observation, and documentation. Research informants were selected through purposive sampling, specifically students who actively use digital media and social media as sources of religious information. Data were analyzed using the Miles, Huberman, and Saldaña model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Islamic digital literacy plays a significant role in shaping attitudes toward.